Kombinasi Elektrokoagulasi dan Adsorbsi dalam Mengolah Air Limbah Industri Batik - Firra Rosariawari; Hermawan Finistyanto (Prosiding ESEC, 2022)
Batik liquid waste has a high dye content and TSS content. This can affect the photosynthetic process of plants and can affect air quality. So that this study aims for the color dissolved in the waste can be adsorbed. The method used in this study is a combination of electrocoagulation and adsorption methods designed to treat and/or reduce pollutant levels, especially TSS and colors contained in batik waste so that it can be disposed of into water bodies. The results of the preliminary test of batik liquid waste on TSS parameters of 460 mg/l, turbidity 151.2 NTU, and color 1245 PTCo. The fixed variables used were contact time for 90 minutes, voltage 12 volts, and size of activated carbon 30 mesh. The result of the electrocoagulation process is that the greater the voltage and the longer the contact time, the higher the percent removal produced. Parameters of TSS message removal were 87.39%, turbidity 71.56%, and color 81.93%. Meanwhile, in the adsorption process, the best results were at 30 mesh size with 39% TSS removal, 69.77% turbidity, and 61.78% color.